Investigation of the Road Noise Source Employing an Automatic Noise Monitoring Station - SZCZODRAK, Maciej; CZYŻEWSKI, Andrzej; KOTUS, Józef (Archives of Acoustics, 2008)
The paper presents a pilot investigation of noise source models in two selected localizations in the context of future dynamic noise map creation. The experiments were carried out using the automatic noise monitoring station engineered at the Multimedia Systems Department of the Gda´nsk University of Technology. The results of the noise measurements employing monitoring stations and its comparison to the reference values are depicted. Short- and longterm studies of noise level are also presented. The experiments described include a comparison between environmental measurement results and the noise level prediction results. Data obtained from the NMPB-96 (Nouvelle Méthode de Prévision du Bruit) and the Harmonoise model data provide the subject of the analysis. The proposed solution of permanent noise monitoring system is also shortly described.